Die rol van die Kerk ten aansien van herstellende geregtigheid in die Suid-Afrikaanse strafregstelsel : 'n teologies-etiese perspektief (Afrikaans) - Van Rooyen, Gert Heldegaard Gerhard (2013)
The title of this mini dissertation is: “The role of the church in respect of restorative justice in the South African criminal justice system: a theological ethical perspective”. The purpose of this study is to investigate the concept of restorative justice from a theological ethical perspective and to see how it is applied in the South African criminal justice system so that it can be determined what role the church can play in this regard. In the South African criminal justice system, the focus has been on the perpetrator and how she/he has come into conflict with the state. The fact that in most crimes, victims are affected by the crime, has traditionally not been taken seriously. In this regard the concept of restorative justice can play a vital role. In the second chapter the concept of restorative justice is explained and it is shown what its relationship to retribution is. Various definitions of restorative justice is then given and it is then shown how restorative justice and the concept of ubuntu are interlinked. In Chapter 3, the role of restorative justice in the South African criminal justice system, is discussed. It is shown that restorative justice is already being implemented at various stages of the criminal justice system and also how the Child Justice Act, Act 75 of 2008, has made restorative justice an essential aspect of the child justice system. It then sets out in Chapter 4 the Biblical basis for restorative justice in both the Old and New Testaments and argues that Biblical justice is essentially restorative in nature. It is pointed out that the foundations of Biblical justice are Shalom, Covenant and Torah. On this basis it is then indicated that Biblical justice is an attribute of God, an object of hope and a primary obligation. It leads to a commitment to action and is a relational reality. Because of this relational aspect, it is then indicated how justice is a restorative activity. The Lex Talionis is then discussed and it is shown how retribution and restoration can walk hand in hand as two sides of the same coin. Jesus and Paul’s understanding of Justice is then discussed. In Jesus’s attitude towards forgiveness and the Lex Talionis, it is shown how the restoration of relationships are of primary concern to him. Paul’s view of Justice is then discussed and it is shown that for him Christ’s death is an act of justice which is driven by his love and therefore also restorative in nature. In the last chapter, the role of the Church in Restorative Justice, is discussed. It is shown how churches can support the Restorative Justice movement and mobilize the community to assist in making restorative justice an integral part of the criminal justice system. Finally, suggestions are made as to how churches (and their members) can get involved with victims and perpetrators of crime. Copyright 2011, University of Pretoria. All rights reserved. The copyright in this work vests in the University of Pretoria. No part of this work may be reproduced or transmitted in any form or by any means, without the prior written permission of the University of Pretoria. Please cite as follows: Van Rooyen, GHG 2011, Die rol van die Kerk ten aansien van herstellende geregtigheid in die Suid-Afrikaanse strafregstelsel : 'n Teologies-etiese perspektief (Afrikaans), MA(Theol) dissertation, University of Pretoria, Pretoria, viewed yymmdd < http://upetd.up.ac.za/thesis/available/etd-03142012-200732 / > C12/4/811/gm === Dissertation (MA(Theol))--University of Pretoria, 2013. === Dogmatics and Christian Ethics === unrestricted